2007
DOI: 10.4093/jkda.2007.31.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Korean Type 2 Diabetic Patients According to Insulin Secretion and Insulin Resistance

Abstract: Background: Korean type 2 diabetic patients are known to differ from western diabetes because of their unique characteristics, such as non-obese but centrally obese anthropometry and relatively more insulin secretory defects than insulin resistance compared to western diabetic patients. Methods:We recruited 1,646 diabetic patients in the present study and excluded the 45 patients with fasting C-peptide < 0.20 nmol/L. We had assessed insulin secretion by fasting serum C-peptide level and insulin resistance by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It has been known that several causes, mainly obesity, environmental factors and inherited metabolic disease, are engaged in type 2 diabetes [ 10 ]. Among diverse metabolic disorders, increased IR and IIS are considered the most critical pathogenetic factors in the development type 2 diabetes [ 6 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that several causes, mainly obesity, environmental factors and inherited metabolic disease, are engaged in type 2 diabetes [ 10 ]. Among diverse metabolic disorders, increased IR and IIS are considered the most critical pathogenetic factors in the development type 2 diabetes [ 6 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that demonstrated the association between genetic variations in the genes coding adiponectin and IR, metabolic syndrome as well as the risk of type 2 diabetes in Korean population [ 10 11 ]. However, not much is known about the CAPN10 genetic polymorphism and metabolic derangements in Koreans.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the proportions of patient with diabetes who are not obese was approximately 71.3% in the early 1980s [ 28 ], 68.5% in the early 1990s [ 29 , 30 ], and 57.5% in the mid-2000s [ 31 ]. These changes represent a decreased proportion of nonobese patients and an increased proportion of obese patients among subjects with diabetes, as well as the westernization of the T2DM phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of diabetes over 30 years old has increased from 6.6% in 1998 to 8.1% in 2005 ( Ministry of Health and Welfare, 1999 ; Ministry of Health and Welfare, 2006 ), and many diabetic experts are predicting that the incidence of diabetes would increase steadily ( Rhee, 2003 ). Most of the Koreans have type 2, non-insulin dependent diabetes mellitus ( Song et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%